The Fragmented Picture of Antimicrobial Resistance in Kenya: A Situational Analysis of Antimicrobial Consumption and the Imperative for Antimicrobial Stewardship - Aarman Sohaili; Judith Asin; Pierre P. M. Thomas (MDPI AG, 2024)
Antimicrobial resistance (AMR) jeopardizes the effectiveness of essential antimicrobial agents in treating infectious diseases. Accelerated by human activities, AMR is prevalent in Sub-Saharan Africa, including Kenya, due to indiscriminate antibiotic use and limited diagnostics. This study aimed to assess Kenya's AMR efforts through a situational analysis of policy efficacy, interventions, and implementation, culminating in recommendations for strengthening mitigation. Employing two methodologies, this study evaluated Kenya's AMR endeavors. A systematic scoping review summarized AMR dynamic, and an expert validated the findings, providing an on-the-ground perspective. Antibiotic resistance is driven by factors including widespread misuse in human medicine due to irrational practices, consumer demand, and substandard antibiotics. Heavy antibiotic use in the agricultural sector leads to contamination of the food chain. The National Action Plan (NAP) reflects a One Health approach, yet decentralized healthcare and funding gaps hinder its execution. Although AMR surveillance includes multiple facets, diagnostic deficiencies persist. Expert insights recognize proactive NAP but underscore implementation obstacles. Kenya grapples with escalating resistance, but commendable policy efforts exist. However, fragmented implementations and complexities persist. Addressing this global threat demands investment in healthcare infrastructure, diagnostics, international partnerships, and sustainable strategies.